The Influence of Honed Surfaces on Metal-on-Metal Hip Joints - Dipankar Choudhury (Japanese Society of Tribologists, 2013)
Wear rate and debris are key problems to implanted metal-on-metal hip joints. Surface texture on bearing surfaces is reported to increase tribological performances. Research on the translation of this technology to metal-on-metal hip joint for reduction of friction, wear rate and debris generation is limited. The aim of this study was to investigate, by theoretical predictions and experimental investigations, the tribological properties of simulated metal-on-metal hip joints with different surface textures. Three different honed surfaces were produced with emery paper at controlled load and speed. The experiments were carried out using a computer-controlled friction simulator. Theoretical prediction was carried out using an existing model for textured surfaces. Both experimental and theoretical results demonstrated that honed surfaces had lower friction coefficients during walking and stairs ascent and descent, demonstrating their potential use in metal on metal hip joints for increased implant longevity.